Peran Pendidikan Kewarganegaraan Dalam Membentuk Etika Kepemimpinan Yang Berkarakter dan Bertanggung Jawab - Dina Andini Nur An-Nisa; Rosi Lantika; Reza Natasha; Thifal Aulia (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
The role of civic education for prospective leaders, especially students, is currently only theoretical, so in this case there is still a lack of practical formation of leadership ethics, as well as theories in civic education are easily ignored because they are not actually proven in learning. That way the role of civic education is quite important to shape the leadership ethics described in theory to be stored in practice. In addition, the role of civic education will facilitate the formation of ethics, so that the process of instilling character morality and responsibility becomes more efficient. The method used in shaping the ethics of leadership with character and responsibility uses a qualitative approach by implementing a critical paradigm. The research results in the form of an analytical tool that can be used for students to facilitate the process of forming values of character and responsibility from the theory of civic education, as well as the formation of leadership ethics into a more practical person. So that it can be concluded that at this time the role of civic education is still carried out in a way of learning that is confined by theory, in which way there is still a risk of saturation, so an analytical tool is needed that can overcome this, which is expected to reduce the existing risks, so that the process of forming leadership ethics with character and responsibility will become a real commitment.